IMPLEMENTATION OF THE CONSTITUTIONAL COURT DECISION NUMBER 65/PUU-VIII/2010 IN THE CRIMINAL JUSTICE SYSTEM - Ummi Khasanah Sitorus Pane; Abdul Madjid; Prija Djatmika (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
The Constitutional Court Decision Number 65/PUU-VIII/2010 provides a new meaning regarding witnesses in the Criminal Procedure Code, by recognizing witnesses as testimonium de auditu. Since the decision was pronounced, the Constitutional Court's decision has come into force and is binding on everyone, especially for the process of investigation, prosecution and trial in court. However, in practice, the Constitutional Court's decision is not followed by judicial bodies under the Supreme Court, in the concrete case of the decision of the West Pasaman District Court No. 191/Pid.Sus/2019/PN Psb which does not consider and decide based on the decision of the Constitutional Court which has become part of the criminal procedural law. In fact, the Constitutional Court Decision Number 65/PUU-VIII/2010 should be legally binding on all.